(untitled) (Research, Society and Development, 2020)
The objective of this study was to report and discuss the current context of the use of emulsifier additives in poultry diets. To accomplish this, literature was searched in main research bases as Web of Science and Google Scholar, scientific papers from the last 20 years that reported this scope focused on poultry nutrition were selected. To keep up with the increase in poultry productive potential, the poultry industry has chosen fat sources to increase the energy content in diets. Lipid intake is essential, not only to meet energy needs, but also to meet the essential requirements in fatty acids, palatability improvement and in the digestibility of other nutrients. In this context, using nutritional tools that improve lipid digestibility is essential, given the importance of this nutrient for animal production. Emulsifiers are active surface agents and their average molecular weight and amphiphilic compounds, which is why emulsifier is absorbed into the interface between oil and water, reduces the surface tension and energy required for emulsion formation. Was proved that sing emulsifiers is a viable alternative with a good propensity of large-scale use, with the aim of reduce the energy levels of diets and, consequently, production costs mainly due to the growth of national poultry farming.